FORMATION AND USE OF MATERIAL RESOURCES AS PART OF THE ECONOMIC POTENTIAL OF AGRICULTURAL ENTERPRISES - Perih Ю. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article examines the formation and utilization of material resources, the essence of economic potential, and the analysis of its effective use by agricultural enterprises. It analyzes the main approaches to leveraging economic potential - specifically resource-based, functional, and productive - within the framework of contemporary trends. New methods for effectively utilizing the resource potential of agricultural enterprises, which serve as the backbone of the agrarian economy, are studied and proposed. Several issues related to the economic essence, characteristics, structure, and utilization of economic potential in agricultural production are also considered. Understanding these methods aids in the development of a strategic mechanism for the effective use of an agricultural enterprise's economic potential. The potential and capabilities of an agricultural enterprise are viewed in the context of executing consistent production and economic activities that can efficiently leverage economic resources to create value, which is reflected in the final outcomes of these operations. It is established that existing interpretations of the economic potential of an enterprise are linked to the resource availability of the business entity and its capacity to organize the usage of available resources in pursuit of its strategic development goals. The article argues that the foundation of key competencies derives from the resource perspective, while the pursuit of strategic development directions stems from a value-oriented perspective. The economic potential of an agricultural enterprise is defined as its ability to effectively conduct economic activities, rationally utilize resources - including natural resources - and adapt to unforeseen circumstances. This involves maximizing the use of available economic resources and the factors influencing their formation in line with the enterprise's development strategy. Additionally, reproductive cycles in agriculture are intricately connected to biological and natural laws. A unique feature of agricultural reproduction is the seasonality of production processes, which is particularly relevant to crop production but can also apply to animal husbandry. This seasonal nature establishes a different procedure for creating working capital and reproducing labor compared to many industrial sectors, as the technological process of producing and selling agricultural products can extend over several months.